ANALISIS SWOT TERHADAP IMPLEMENTASI PEMBELAJARAN TERPADU PADA MI MUHAMMADIYAH 1 SLINGA PURBALINGGA - Novan Ardy Wiyani; Rosika Priasih (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2022)
To find out in depth about the implementation of integrated learning, we need a through analysis. SWOT (Strength, Weakness, Opportunities, and Threatment) is a kind of analysis that we use.With a SWOT analysis, the author examines the various strengths, weaknesses, opportunities, and challenges that exist and have an impact on the implementation of integrated learning. This type of research is a qualitative descriptive research. Descriptive research in this study is used to describe how the implementation of integrated learning using SWOT analysis. The research was conducted at MI Muhammadiyah 1 Slinga, Kaligondang District, Purbalingga Regency. The data collection procedure was carried out through observation, interviews with parties involved andinfluencing the implementation of integrated learning, and documents relevant to the research. Data were analyzed using data reduction steps, data display and drawing conclusions. Checking the validity of the data is done by using triangulation techniques and sources. Research uncovers various strengths, weaknesses, and challenges. In general, the implementation of thematic/integrated learning based on the results of the SWOT analysis at MI Muhammadiyah 1 Slinga is still not optimal. Some teachers still do not master the technology, and the infrastructure does not support it. Besides, the teacher also still has difficulty in integrating and linking between subjects.